(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Skeletal muscle relaxants (SMRs) are drugs that reduce the muscle tone either by acting peripherally at the neuromuscular junction (neuromuscular blockers) or centrally in the cerebrospinal axis or directly on the contractile mechanism. They reduce the spasticity in a variety of neurological conditions and are also useful in surgeries.